Genome‐wide association of drought‐related and biomass traits with HapMap SNPs in Medicago truncatula - Kang, Yun; Sakiroglu, Muhammet; Krom, Nicholas; Stanton‐Geddes, John; Wang, Mingyi; Lee, Yi‐Ching; Young, Nevin D.; Udvardi, Michael (Plant, cell and environment, 2015)
Improving drought tolerance of crop plants is a major goal of plant breeders. In this study, we characterized biomass and drought‐related traits of 220 Medicago truncatula HapMap accessions. Characterized traits included shoot biomass, maximum leaf size, specific leaf weight, stomatal density, trichome density and shoot carbon‐13 isotope discrimination (δ13C) of well‐watered M. truncatula plants, and leaf performance in vitro under dehydration stress. Genome‐wide association analyses were carried out using the general linear model (GLM), the standard mixed linear model (MLM) and compressed MLM (CMLM) in TASSEL, which revealed significant overestimation of P‐values by CMLM. For each trait, candidate genes and chromosome regions containing SNP markers were found that are in significant association with the trait. For plant biomass, a 0.5 Mbp region on chromosome 2 harbouring a plasma membrane intrinsic protein, PIP2, was discovered that could potentially be targeted to increase dry matter yield. A protein disulfide isomerase‐like protein was found to be tightly associated with both shoot biomass and leaf size. A glutamate‐cysteine ligase and an aldehyde dehydrogenase family protein with Arabidopsis homologs strongly expressed in the guard cells were two of the top genes identified by stomata density genome‐wide association studies analysis. Drought is a major impediment to maximal yield in crop plants. We performed genome‐wide association analyses of eight biomass and drought‐related traits in 220 M. truncatula HapMap accessions using various statistical models. For each trait, we identified candidate genes and chromosome regions containing markers that are in significant association with the trait, which could be targeted for breeding purposes to enhance crop drought tolerance.